Benchmarking a Canadian anesthesiology resident research program against national norms using a logic model framework: A quality improvement study - Barbour-Tuck, Erin; Mutter, Thomas; O'Brien, Jennifer M; Girling, Linda; Choo, Eugene; Gamble, Jonathan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: Canadian specialty training programs are expected to deliver curriculum content and assess competencies related to the CanMEDS Scholar role. We evaluated our residency research program and benchmarked it against national norms for quality improvement purposes.Methods: In 2021, we reviewed departmental curriculum documents and surveyed current and recently graduated residents. We applied a logic model framework to assess if our program’s inputs, activities, and outputs addressed the relevant CanMeds Scholar competencies. We then descriptively benchmarked our results against a 2021 environmental scan of Canadian anesthesiology resident research programs.Results: Local program content was successfully mapped to competencies. The local survey response rate was 40/55 (73%). In benchmarking, our program excelled in providing milestone-related assessments, research funding, administrative, supervisory, and methodologic support, and requiring a literature review, proposal presentation, and local abstract submission as output. Acceptable activities to meet research requirements vary greatly among programs. Balancing competing clinical and research responsibilities was a frequently reported challenge.Conclusions: The logic model framework was easily applied and demonstrated our program benchmarked well against national norms. National level dialogue is needed to develop specific, consistent scholar role activities and competency assessments to bridge the gap between expected outcome standards and education practice.